2010
DOI: 10.1186/1476-0711-9-24
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia infection among women visiting a gynaecology outpatient department: evaluation of an in-house PCR assay for detection of Chlamydia trachomatis

Abstract: BackgroundScreening women for Chlamydia trachomatis infection in developing countries is highly desirable because of asymptomatic infection. The existing diagnostic methods in developing countries are not effective and their sensitivity fall below 45.0% which leads to further spread of infection. There is an urgent need for improved and cost effective diagnostic tests that will reduce the burden of sexually transmitted infections in the developing world.MethodsPrevalence of C. trachomatis infection among women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 43 publications
(47 reference statements)
1
31
2
3
Order By: Relevance
“…Codes et al [22] found a prevalence of 6.9 % of Chlamydia in asymptomatic women. Patel et al [23] found a large prevalence of 23 % of Chlamydia in woman visiting gynecology department of Hindu Rao hospital in Delhi. The authors attribute the high prevalence to better detection procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Codes et al [22] found a prevalence of 6.9 % of Chlamydia in asymptomatic women. Patel et al [23] found a large prevalence of 23 % of Chlamydia in woman visiting gynecology department of Hindu Rao hospital in Delhi. The authors attribute the high prevalence to better detection procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Portanto, visto que é um agente com alta prevalência no mundo, faz-se necessário o emprego de metodologias de diagnóstico e monitoria adequada da CT (1) . Entre a vasta gama de metodologias, a mais utilizada é a identificação por métodos sorológicos (9,28) , no entanto, é fundamental o emprego de metodologias da Biologia Molecular na identificação, principalmente pelo material genético, do agente, entre elas destaca-se a PCR (2,6,8,10,12,22,25,27,(30)(31)(32) , por possuir eficácia e sensibilidade de 100%, enquanto o imunoensaioenzimático, por exemplo, possui sensibilidade de 58,8% e especificidade de 100% (14) .…”
Section: Introductionunclassified
“…The largest number of new cases (42.89 million) occurred in the region of South and Southeast Asia, accounting for 47z of the total infected cases. The prevalence of C. trachomatis infection diagnosed by polymerase chain reaction (PCR) using genital specimens among women in India was reportedly 23z-32z (2,3). In Bangladesh, there have been some studies on the prevalence of C. trachomatis infections, which examined only female sex workers (FSW) in Dhaka or other cities (4)(5)(6)(7).…”
mentioning
confidence: 99%